Characterization of Seven Chickpea Genotypes Using Correlation, Path and Cluster Analysis - Hama-Ali, Emad Omer (Sulaimani Journal for Pure and Applied Sciences, 2018)
Selecting genotype and sowing strategies vary with environment and consider as an important cultural practice for chickpea production. This research was carried out during 2015-2016 season at Qlyasan Agricultural Research Station/College of Agricultural Sciences/University of Sulaimani. Randomized Completely Block Design (RCBD) with three replicates was used to study the effect of sowing dates (winter 12th December 2015 and spring 17th February 2016) on seven chickpea genotypes received from ICARDA for some agronomic characteristics including the yield. The results confirm the effectiveness of winter sowing date for all of the studied characters compared to their planting in spring. FLIP 05-150C genotype gave the best values for most of the studied characters. Seed yield/plant was positively and high significantly p < 0.01 affected by plant height (0.834), plant weight (0.968), number of branches/plant (0.889) and number of pod/plant (0/931). Number of pods/plant recorded the maximum positive direct effect on seed yield/plant (0.711); followed by plant weight (0.416) In contrast, number of branches/plant recorded the maximum negative direct effect with (-0.302). Whereas the maximum positive indirect effect was recorded by plant weight and number of branches/plant via a number of pod/plant with 0.646 and 0.648 respectively, while the maximum negative indirect effect values were recorded by plant height (-0.242), plant weight (-0.281) and number of branches/plant (-0.302) via a number of branches/plant. Cluster analysis indicated three groups in both sowing dates depending on the studied traits. Finally the result demonstrated that winter sowing is very promising for this region.
Keywords: Chickpea; path analysis; cluster analysis; Genetic diversity